Penerjemahan Kanyouku dalam Novel Shikisai wo Motanai Tazaki Tsukuru to Kare no Junrei no Toshi Karya Haruki Murakami - Dwiyanti, Febri Nur; ., Hermandra; Suri, Intan (Humanis; Vol 26 No 1 (2022), 2022)
Idioms in Japanese are called kanyouku. This study aims to describe the kanyouku translation strategies and procedures contained in the novel. The theory used in this study are the theory of idiom translation strategy according to Baker (1992) and the theory of translation procedures according to Vinay & Darbelnet in Venuti (2000). This research is a qualitative descriptive research. The data in this study are the kanyouku of the upper limbs contained in the novel Shikisai wo Motanai Tazaki Tsukuru to Kare no Junrei no Toshi (2013) by Haruki Murakami and its translation in Indonesian "Tsukuru Tazaki Without Color and the Year of His Pilgrimage" (2018) which is translated by Ribeka Ota. From the result of the analysis of 35 kanyouku it was found that the kanyouku translation strategy used by the translator was a strategy using an idiom of similar meaning and form and a paraphrasing strategy. While the translation procedures used are literal translation, transposition and equivalence.